FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Febiola, Febiola; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2024)
The purpose of this research is to determine the effect of the capital structure, profitability, firm size and firm age on firm value in manufacturing companies listed on the Indonesia Stock Exchange in the period 2017 – 2019. The sample was selected by purposive sampling method and there were 89 companies that met the criteria. This study uses Microsoft Excel program to input and calculate data while data processing uses SPSS 25. The results of this study show that the capital structure, profitability and age of the firm have a significant positive effect on firm value, while firm size has no significant positive effect on firm value.